2017
DOI: 10.1016/j.aap.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in cognitive functioning predict effectiveness of a heads-up lane departure warning for younger and older drivers

Abstract: The effectiveness of an idealized lane departure warning (LDW) was evaluated in an interactive fixed base driving simulator. Thirty-eight older (mean age = 77 years) and 40 younger drivers (mean age = 35 years) took four different drives/routes similar in road culture composition and hazards encountered with and without LDW. The four drives were administered over visits separated approximately by two weeks to examine changes in long-term effectiveness of LDW. Performance metrics were number of LDW activations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 38 publications
0
14
1
Order By: Relevance
“…The ability to quickly and accurately process, and act upon, spatial information is an essential component of safe driving in young and older adults alike. Research surrounding the use of in-car automatic lane departure warning software has identified that lane-departure warnings are generally activated more often in older adults than in young [ 39 ]. However, spatial asymmetries are difficult to study in driving behaviour due to the potential confound of learned behaviour associated with left- or right-lane driving experience.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to quickly and accurately process, and act upon, spatial information is an essential component of safe driving in young and older adults alike. Research surrounding the use of in-car automatic lane departure warning software has identified that lane-departure warnings are generally activated more often in older adults than in young [ 39 ]. However, spatial asymmetries are difficult to study in driving behaviour due to the potential confound of learned behaviour associated with left- or right-lane driving experience.…”
Section: Introductionmentioning
confidence: 99%
“…Sample sizes ranged from 11 to 257 participants. Studies were conducted in nine countries including the United States ( n = 14) (Aksan et al, 2017; Aksan et al, 2015; Becic, Manser, Drucker, & Donath, 2013; Brown, He, Roe, & Schnell, 2010; Kidd & Buonarosa, 2017; Kramer, Cassavaugh, Horrey, Becic, & Mayhugh, 2007; Lester et al, 2015; D. C. Marshall, Wallace, Torner, & Birt-Leeds, 2010, 2011; Mok, Johns, Gowda, Sibi, & Ju, 2016; Oh, Ko, & Ji, 2016; Reimer, Mehler, & Coughlin, 2016; Strayer, Cooper, Turrill, Coleman, & Hopman, 2016; Sullivan, Tsimhoni, & Bogard, 2008), Netherlands ( n = 4) (Davidse, Hagenzieker, van Wolffelaar, & Brouwer, 2009; Dotzauer, Caljouw, de Waard, & Brouwer, 2013, 2015; Dotzauer, de Waard, et al, 2015), Germany ( n = 3) (Gelau, Sirek, & Dahmen-Zimmer, 2011; Haberstroh, Klingender, Ramakers, & Henning, 2010; Kazazi, Winkler, & Vollrath, 2015), Japan ( n = 2) (Hibino, Kobayashi, Daimon, & Oda, 2013; Saito & Raksincharoensak, 2016), Canada ( n = 1) (Caird, Chisholm, & Lockhart, 2008), United Kingdom ( n = 1) (Guo, Blythe, Edwards, Pavkova, & Brennan, 2015), France ( n = 1) (Bruyas & Simões, 2010), Australia ( n = 1) (Yi, Lee, Parsons, & Falkmer, 2014), and Czech Republic ( n = 1) (Novotny & Bouchner, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Sample sizes ranged from 11 to 257 participants. Studies were conducted in nine countries including the United States (n = 14)(Aksan et al, 2017;Aksan et al, 2015;Becic, Manser, Drucker, & Donath, 2013;Brown, He, Roe, & Schnell, 2010;Kidd & Buonarosa, 2017;…”
mentioning
confidence: 99%
“…These estimates are based on a best-case scenario where all drivers "react ideally to the warnings issued by the system" (Kuehn et al, 2009). In practice, the actual observed safety impact of ADAS is dependent on "human factor issues" such as driving behavior and capabilities (Aksan et al, 2017 andKuehn et al, 2009). Individual driving factors must be adequately accounted for in order to more accurately quantify the safety potential of ADAS (Kuehn et al, 2009).…”
Section: Motivating Data Examplementioning
confidence: 99%
“…Determining the population specific safety improvement of ADAS would be relevant to several industries. There is preliminary evidence to suggest ADAS may not benefit all drivers or may need to be altered for certain populations (Aksan et al, 2015, Aksan et al, 2016, and Aksan et al, 2017. Vehicle manufacturers and insurance providers could use the information to tailor safety warnings to individual drivers.…”
Section: Motivating Data Examplementioning
confidence: 99%